Do free radical NETwork and oxidative stress disparities in African Americans enhance their vulnerability to SARS-CoV-2 infection and COVID-19 severity? (2020)
This review focuses on the hypothetical mechanisms for enhanced vulnerability of African Americans to SARS-CoV-2 infection, COVID-19 severity, and increased deaths. A disproportionately higher number of African Americans are afflicted with autoimmune and inflammatory diseases (e.g., diabetes, hypertension, obesity), and SARS-CoV-2 has helped expose these health disparities. Several factors including socioeconomic status, inferior health care, and work circumstances contribute to these disparities. Identifying potential inflammatory biomarkers and decreasing basal levels in high-risk individuals with comorbidities through preventive measures is critical. Immune cells, particularly neutrophils, protect us against pathogens (bacteria, fungi, and viruses) through increased generation of free radicals or oxidants and neutrophil extracellular traps (NETs) that ensnare pathogens, killing them extracellularly. However, continued generation of NETs coupled with the lack of prompt removal pose danger to host cells. NET levels are increased during pro-inflammatory diseases. COVID19 patients exhibit elevated NET levels, depending upon disease severity. Conceivably, highrisk individuals with elevated basal NET levels would exhibit hyper-inflammation when infected with SARS-CoV-2, amplifying disease severity and deaths. Drugs inhibiting oxidant formation and vitamin supplements decreased NET formation in mice models of inflammation. Thus, preventive treatments lowering NET levels and inflammation in high-risk individuals could mitigate SARS-CoV-2-induced complications and decrease mortality.